Pharmaceutical salts of the antidepressants Paroxetine and Fluoxetine, selective serotonin reuptake inhibitors: crystal engineering, solid-state characterization and thermodynamic aspects - Carvalho Júnior, Paulo de Sousa (2016)
The development of new solid forms of active pharmaceutical ingredients (API) is relevant both from fundamental as well as industrial perspectives. To this end, Crystal Engineering plays an ever-increasing important role in pharmaceutical sciences. Among the crystal engineering strategy, salt formation is the most important and implemented approach. The salt forms of API could be used to modulate and tuned the solubility and stability of API to provide optimal practical uses. Herein, we report pharmaceutical salts of two Selective Serotonin Reuptake Inhibitor antidepressants used in the treatment of depression and anxiety disorders, Paroxetine (PRX) and Fluoxetine (FLX). For this purpose, salt formers, supramolecular synthesis and crystallization protocols have been driven by the systematization of structural and supramolecular data of molecules and analogues from the Cambridge Structural Database. Paroxetine bromide hemihydrate ((PRXBr)0.5H2O), Paroxetine Nitrate hydrate (PRXNO3H2O) and two polymorphs of Fluoxetine Nitrate (FLXNO3) have obtained. All were characterized by a combination of techniques including Single Crystal X-ray Diffraction, Differential Scanning Calorimetry (DSC), Thermogravimetry analysis (TGA), Hot Stage Microscopy, Fourier transform infrared spectroscopy (IR) and solubility measurements. Since the hydration/dehydration process in APIs induces phase transitions that compromise its efficiency, the structural characterization of (PRXBr)0.5H2O help to understand its reversible dehydration process. Also, this study has implication in the understating of dehydration of isostructural PRX hydrochloride salt. Additionally, the (PRXNO3)H2O have shown the conformational flexibility and supramolecular diversity of PRX. On the other hand, the chirality of FLX is related to two nitrate salt polymorphs. A racemate and a non-centrosymmetric structure with independent enantiomers in the asymmetric unit were obtained for FLXNO3. Their packing have shown the existence of different racemic motifs, resulting in different enantiomer orientations The rare occurrence of racemic systems in non-centrosymmetric space groups becomes this event a noteworthy case. By their physicochemical properties, the polymorphs were monotropically related. The scientific contributions of this thesis show the diversity of the solid forms and define candidates to new antidepressants APIs solid formulations.